Rancang Bangun Sistem Point Of Sale Berbasis Mobile untuk Meningkatkan Produktivitas Usaha - Muhamad Sadali; Yupi Kuspandi Putra; Andri Wahyu Anugrah (Fakultas Teknik Universitas Hamzanwadi, 2023)
The point of sale (POS) system is not something foreign to prominent entrepreneurs, this system has long been used by large-scale business actors, but generally, a system like this has complex features and its operation requires special personnel, therefore in the all-digital era Currently, there are still many small entrepreneurs using traditional processes in managing their businesses due to limited access to technology and costs, this will undoubtedly take time and reduce business productivity compared to using modern management systems. Then we need a POS that is easier to access and does not require large costs by small or medium-scale businesses, because it will be the right solution for business management with a lot of manual work automated by the system, such as profit and loss calculations, information on the availability of goods, information on quantities goods, and transaction processes using a scan code where the total payment and change will be calculated automatically by the system, of course with the presence of this point of sale system it will make it easier for small and medium business actors because the system is available in the form of mobile application which can be accessed easily by many business groups.